2018
DOI: 10.1039/c8sc02815j
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-dependent selectivity in sulfonium ylide cycloisomerization reactions

Abstract: An unusual example of π-acid catalyst-dependent selectivity in the cycloisomerization of alkene-tethered sulfonium ylides affords cyclopropanes or dihydrofurans with excellent control of chemoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Recently, the group of Maulide also reported the cyclopropanation of sulfur ylides with S-tethered olefins. 355 The cyclopropanation of sulfur ylide 623 , carrying two olefins, showed high selectivity for the S-tethered olefin, affording product 624 in 75% yield (Scheme 110). Interestingly, the authors describe a catalyst-dependent cyclization, where other π-acidic catalysts such as Pd(II) and Pt(II) salts selectively afforded dihydrofuran 625 in moderate to excellent yields.…”
Section: Sulfur Ylidesmentioning
confidence: 99%
“…Recently, the group of Maulide also reported the cyclopropanation of sulfur ylides with S-tethered olefins. 355 The cyclopropanation of sulfur ylide 623 , carrying two olefins, showed high selectivity for the S-tethered olefin, affording product 624 in 75% yield (Scheme 110). Interestingly, the authors describe a catalyst-dependent cyclization, where other π-acidic catalysts such as Pd(II) and Pt(II) salts selectively afforded dihydrofuran 625 in moderate to excellent yields.…”
Section: Sulfur Ylidesmentioning
confidence: 99%
“…[24] Whilst the majority of the initial studies wereb ased on non-stabilized sulfonium and sulfoxonium ylides, modern work exploits the reactivityo f their stabilized surrogates, in which electron density from the ylidic carbon is distributed to one or two electron-withdrawing functionalities. This in turn enables the utilization of these sulfur ylides as practical and bench-stable reagents as well as the development of novel reactivity.I ndeed, applicationso f stabilized sulfonium and sulfoxonium ylides have been expanded to encompass noble transition metal catalysis, [8,9,25] in particularAu I .…”
mentioning
confidence: 99%
“…Recently,our group has reported that gold-catalyzed electrophilic activation of alkenes allows the construction of highly functionalized cyclopropane scaffolds. [25][26][27][28][29][30] Prior to that, we [31] and others [32] have demonstrated the synthesis of multisubstituted furan cores throughg old-catalyzed activation of alkynes in the presence of sulfonium ylides, either in intra-or intermolecular fashion. Interestingly,t he majority of these and related transition metal-catalyzed reactions of sulfur ylides mostly employ variations on substituents tethered to the ylidic carbon.O nt he other hand, only minor variations on the sulfur substitution have been reported, [25,30] probably due to the fact that most of those transformationse ventually result in elimination of the sulfur tether during the reaction, thus, leading to stoichiometric sulfide byproducts (cf.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfonium and sulfoxonium ylides have witnessed a renaissance in contemporary catalysis beyond the well‐known Johnson–Corey–Chaykovsky reactions,8 namely in C−H functionalisation,9 N−H insertion,10 and cycloisomerisation reactions 11. Their popularity is owed to the fact that they are easy to prepare, readily purified, and considerably safer to handle than their diazo counterparts.…”
mentioning
confidence: 99%